Rheological Investigation of Bitumens Obtained From Different Refineries Modified With SEBS: Response Surface Methodology (RSM) Analysis - Yalçın, Erkut; Özdemir, Ahmet Münir (Avestia Publishing, 2025)
The durability and performance of hot mix asphalts are highly dependent on the rheological properties of the bitumen. However, the diversity in the composition of crude oil from different regions, combined with the effects of the refining process, leads to significant differences in the properties of bitumen. This shows that modification methods can produce different results for each type of bitumen. Bitumen modification, especially with elastomeric additives, is an effective method to improve the deformation resistance and long-term performance of asphalt pavements. In this study, bituminous binders of penetration class 160/220 were obtained from two different refineries in Turkey-Batman and Iraq-Lanaz. Bitumens were modified with SEBS at different percentages (2,3 and 4%) and their rheological properties were determined by Dynamic Shear Rheometer (DSR) test. The effect of temperature and additive ratios on bitumens of different origin was investigated by Response Surface Methodology (RSM) analysis. The results revealed the importance of bitumen origin and showed that the addition of SEBS significantly increased the rutting strength for both binder types. The RSM analysis revealed that the effect of temperature was higher than that of the additive. © 2025 Avestia Publishing. All rights reserved.
10th World Congress on Civil, Structural, and Environmental Engineering, CSEE 2025 -- 10 April 2025 through 12 April 2025 -- Barcelona -- 330019
Keywords: Bitumen origin; modification; Response Surface Method (RSM); SEBS